Effects of reforestation with Quercus species on selected arthropod assemblages (Isopoda Oniscidea, Chilopoda, Coleoptera Carabidae) in a Mediterranean area - Baini, Francesco; Pitzalis, Monica; Taiti, Stefano; Taglianti, Augusto Vigna; Zapparoli, Marzio; Bologna, Marco a (Forest Ecology and Management, 2012)
Arthropod assemblages (Isopoda Oniscidea, Chilopoda, Coleoptera Carabidae) were studied in three 20- year-old reforestations with native oak species (holm-oak Quercus ilex, Turkey-oak Quercus cerris, and downy-oakQuercus pubescens) and in a natural mixed oak forest (Q. cerris andQuercus frainetto) in Latium (central Italy). The three reforested areas had been previously used for agricultural purposes. Samples were collected monthly by pitfall traps for a period of 1 year (March 2009–February 2010). Structural parameters and the arthropod assemblage compositions of the four studied areas were compared. The effects of the different forest types and the inﬂuence of environmental variables on the activity density of each species were analyzed, with particular emphasis to forest species. Contrary to centipedes and ground beetles, woodlice showed lower values of richness, diversity and equitability in reforestations than in the natural forest. According to Canonical Correspondence Analysis, forest species of woodlice and centipedes resulted mainly associated with forests characterized by a high structural heterogeneity (natural forest and reforestation with Q. pubescens). In these two forests the activity density of centipede forest species is mainly inﬂuenced by the coverage of both shrub and leaf litter layer, and woodlice forest species only by the coverage of the latter. The ground beetle forest species were mainly associated with forests characterized by low structural heterogeneity and an almost total closure of the canopy throughout the year (reforestation with Q. ilex). However, some ground beetle forest species are present also in the natural forest. Our results suggest that reforestations with different native broadleaf species belonging to the local ‘‘potential’’ vegetation can contribute to the conservation of the diversity of forest arthropod assemblages in the extremely fragmented agricultural landscape of the middle Tyrrhenian area
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Anthropogenic habitats; Assemblages; Central Italy; Pitfall trapping; Soil fauna